2017
DOI: 10.1002/car.2488
|View full text |Cite
|
Sign up to set email alerts
|

Media Coverage, Public Awareness and State Intervention in Child Abuse in China – An Analysis of High‐Profile Cases

Abstract: Key Practitioner Messages Child abuse is a complex social problem that is often deeply rooted in the cultural, economic and social practices of the country in which it exists. Child abuse in China is understood as deliberate and harmful acts, while many Western societies also include acts of omission such as neglect. There is a complex relationship between public awareness, media coverage and state intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…We are all increasingly aware of the power of the media in influencing public opinion and policy discourse (Lonne and Parton, ; Qiao et al ., ). Those taking lead roles in child protection in all organisations have to know how to deal with the media and engage in strategic communication around safeguarding and child protection (Royal College of Nursing, ).…”
Section: Media Coverage In Child Protectionmentioning
confidence: 99%
“…We are all increasingly aware of the power of the media in influencing public opinion and policy discourse (Lonne and Parton, ; Qiao et al ., ). Those taking lead roles in child protection in all organisations have to know how to deal with the media and engage in strategic communication around safeguarding and child protection (Royal College of Nursing, ).…”
Section: Media Coverage In Child Protectionmentioning
confidence: 99%
“…Our next two papers both explore child maltreatment in China – the most populous nation on Earth and one where the issues facing practitioners and policymakers may be very different from those in the West. As Dong Ping Qiao and colleagues () point out,
‘China is currently in a period of social transformation, which has seen large‐scale migration from rural communities to large cities… This has led to changes in traditional family structures, child‐rearing practices and social stability as the capacity of families to protect their children has been put under pressure.’ (p. 379)
…”
Section: Child Maltreatment In Chinamentioning
confidence: 99%
“…Or, as in one of the cases cited by Qiao et al . (), to fend for themselves as best they can. The authors cite Duan et al .…”
Section: Child Maltreatment In Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…Another paper, this time from mainland China and available online through Early View explores how public attitudes to the issue of child maltreatment have changed over recent years (Qiao et al, 2017). After they analysed 3565 relevant news reports during 2010-15, Qiao et al revealed that the cases which were most frequently reported had been those with serious physical harm to children.…”
mentioning
confidence: 99%